GERAKAN BUDAYA DALAM PENGENTASAN KEMISKINAN (Kajian Implementasi Gerakan Segoro Amarto Pada Pemerintah Kota Yogyakarta) - , Sahrony A. Hirto, Prof. Dr. Muhadjir Darwin, M.PA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Poverty reduction is now the author can describe in three ways. The first, the equation or uniform policy in each region. Second, the sectoral ego and lack of synchronization of the various policies implemented by the department or ministry of state. And the Third, poverty reduction programs have tended to focus on social aid efforts for the poor. Given the importance of poverty reduction, the government seeks to elaborate Yogyakarta poverty policy by using social capital as a driving force, the policy is called the Movement Segoro Amarto (Spirit of Mutual Cooperation Agawe Majune Ngayogyakarto). Once inaugurated by the Governor of Yogyakarta in 2010 the Movement Segoro Amarto tested in three villages called Segoro Amarto village, the village is a village Kricak, Tegalpanggung and Sorosutan. This study is intended to look at the emergence of culture in society through poverty alleviation policies. In addition, this study also look at the response to the policy group Segoro Amarto basis. Based on the results collected in the field into two authors conclude, among other things: First Segoro Amrto specific implementation for urban pilot projects implemented through the help of the governor is given directly to the village. Second, the policy response to the base group also varied Segoro Amarto assume that there is a concern Segoro Amarto a king to the people. In addition, some people also assume that Segoro Amarto is a government program intended to provide assistance to the poor, and for a fraction interpret that this movement to instill the value of discipline, mutual cooperation, solidarity and concern.